Improving Flat Building Learning Outcomes Through a Jigsaw Model Based on Culturally Responsive Teaching in Grade IV Elementary School - Triwahyudianto, Triwahyudianto; Septiana, Eva Wulan; Suprianti, Dhia (Sistem-Among : Jurnal Pendidikan Sekolah Dasar, 2025)
The mathematics learning outcomes of Grade IV students at Sekolah Dasar Negeri Bandungrejosari 3 in Malang City on the topic of flat buildings remain relatively low and uneven due to a learning approach that does not sufficiently respond to students’ cultural, social, and prior learning experiences. This study aims to improve mathematics learning outcomes through the application of the Jigsaw learning model based on Culturally Responsive Teaching. The Jigsaw model promotes collaboration, active participation, and individual responsibility within heterogeneous groups, while the principles of Culturally Responsive Teaching are integrated to create learning that is contextual, culturally relevant, and respectful of student diversity. This research employed classroom action research conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The research subjects were 28 students in Grade IV. Data were collected through learning outcome tests, student activity observation sheets, and field notes. The results showed that applying the Jigsaw model based on Culturally Responsive Teaching was effective in increasing student activeness, confidence, and conceptual understanding of flat buildings. The completeness of students’ learning outcomes increased from 35.71 percent in the pre-cycle to 71.43 percent in the first cycle and reached 92.86 percent in the second cycle, with the average score also showing a significant improvement. These findings demonstrate that the combination of the Jigsaw model and Culturally Responsive Teaching can create an inclusive learning environment, adapt to classroom diversity, and effectively improve mathematics learning outcomes in elementary schools.